A status report on the hybrid metal extrusion & bonding (HYB) process and its applications. Issue 2 (21st February 2019) - Grong, Øystein; Sandnes, Lise; Berto, Filippo
Abstract: The hybrid metal extrusion & bonding (HYB) process is a patented solid‐state joining method for metals. Over the years, it has evolved into a multi‐functional joining process handling a wide range of joint configurations (butt, fillet, and slot welds) and base metal combinations (Al, Fe, Ti, and Cu). At present, up to four different metals can be joined together in one pass using the HYB PinPoint extruder and AA6082 as filler wire.